1994
DOI: 10.1128/jb.176.8.2439-2443.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a chromosomal gene cluster, pah, that encodes the upper pathway for phenanthrene and naphthalene utilization by Pseudomonas putida OUS82

Abstract: A 25-kb DNA SalI fragment cloned from the chromosomal DNA of Pseudomonas putida OUS82, which utilizes phenanthrene (Phn+) and naphthalene (Nah+), carried all of the genes necessary for upper naphthalene catabolism. Cosmid recombinant pIP7 complemented both the Nah- and Phn- defects of OUS8211 (Trp-Nah-Phn-Sal+[salicylate utilizing]Hna+[1-hydroxy-2-naphthoate utilizing]) and only the Phn- defect of OUS8212 (Trp-Nah-Phn-Sal-Hna+). The results indicate that strain OUS82 uses different pathways after o-hydroxycarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 30 publications
1
81
0
Order By: Relevance
“…The resultants dihydrodiol is then sequentially attacked by dehydrogenase and meta-cleavage enzyme. These reaction are considered to yield 1-hydroxy 2-napthoic acid (Pinyakong et al, 2000;Kiyohara et al, 1994). These finding suggested that the same of the enzyme could convert chrysene via intial dioxygenation at 1,2 and 2,3-position to obtain isolated compound I. Fusarium sp.…”
Section: Evaluation Of Enzyme Activitymentioning
confidence: 89%
“…The resultants dihydrodiol is then sequentially attacked by dehydrogenase and meta-cleavage enzyme. These reaction are considered to yield 1-hydroxy 2-napthoic acid (Pinyakong et al, 2000;Kiyohara et al, 1994). These finding suggested that the same of the enzyme could convert chrysene via intial dioxygenation at 1,2 and 2,3-position to obtain isolated compound I. Fusarium sp.…”
Section: Evaluation Of Enzyme Activitymentioning
confidence: 89%
“…High levels (Ϸ90%) of homology and a conserved gene arrangement are observed in the nah, ndo, pah, and dox sequences (63,64,147,333,355,601). In fact, it has been proposed that the dox plasmid, which encodes a dibenzothiophene (DBT) metabolic pathway analogous to the naphthalene catabolic pathway, may in fact be a naphthalene catabolic plasmid (163).…”
Section: Aerobic Pah Metabolismmentioning
confidence: 99%
“…Salicylate and 1-hydroxy-2-naphthoate are further degraded by other catabolic enzymes. The enzymes in the upper pathway have broad substrate specificities, and various polycyclic aromatic hydrocarbons other than naphthalene and phenanthrene are oxidized by a high-density suspension of OUS82 cells (9).…”
mentioning
confidence: 99%
“…tac promoter expression vector pKK223-3 (1) was purchased from Pharmacia LKB Biotechnology, Uppsala, Sweden. The rich medium (LB) and the minimal medium used in this study were described previously (9). SMT medium was the minimal medium plus 0.3% disodium succinate and 30 ,g of tryptophan per ml.…”
mentioning
confidence: 99%
See 1 more Smart Citation